THE IMPLEMENTATION OF JUSTICE PRINCIPLE WITHIN THE LAND PROCUREMENT FOR PUBLIC UTILITIES CONSTRUCTION - SH, Sahnan, (Jurnal IUS (Kajian Hukum dan Keadilan), 2015)
The Indonesiaâs population growth and development increasing makes all parties, in the reality, need more land, especially for government. Land procurement for public utilities construction usually have a problem, because on the process we rarely meet easy process or easy getting deal between landowner and government, or other parties who needs the land.Â  This occurs because is difficult getting deal between government and landowner about compensation. Justice principle implementation sometimes violated and take it for granted by government or other parties who need the land. The landowner usually assumes total compensation they accept tends not give fairness. This research have purpose as follows (1) To enquiry and analyze justice principle implementation of land procurement for public utilities construction, and (2) To make us know, what kind factor makes justice principle implementation land procurement for public utilities construction difficult to implemented, and to make us know what government should do to fix these. This research is normative research, Normative research is studying norm, like justice principle and conceptual norms that regulated land procurement for public utilities construction.The result of this research consist of implementation of justice principle ofÂ  land procurement for public utilities construction can not touch sense of justice society. This occurs because government gives compensation, far from they want, far from fairness, and far from properness. That is why sometime we not surprise on the implementation creates conflict between landowner and government or landowner and company who needs the land.Keywords: Justice principle implementation